6 - -12 = 18
-6 x -3 = 18 + (-6) = 12
18
-6
(-6) x (-3) = 18 (-10) x (-9) = 90 18 - 90 = -72
6 - -12 = 18
-6 x -3 = 18 + (-6) = 12
It is already in that form if the hyphens are taken as minus signs as 18-6-6-6 = 0. The possible restatement would be 18-(3)(6)=0. The written form would be "Eighteen minus six, minus six, minus six, equals zero."
18
-6
(-6) x (-3) = 18 (-10) x (-9) = 90 18 - 90 = -72
3 minus 3/18 is 2 5/6
6 - -12 = 18
it is 18+(-3)-6=18-3-6=18-9=9.thus the answer is 9
-18
6-18= -12 -12/6= -2 -2x2= -4 answer= -4
It is: -6-12 = -18